2017
DOI: 10.1007/s11914-017-0348-1
|View full text |Cite|
|
Sign up to set email alerts
|

Microcephalic Osteodysplastic Primordial Dwarfism, Type II: a Clinical Review

Abstract: Purpose of the ReviewThis review will provide an overview of the microcephalic primordial dwarfism (MPD) class of disorders and provide the reader comprehensive clinical review with suggested care guidelines for patients with microcephalic osteodysplastic primordial dwarfism, type II (MOPDII).Recent FindingsOver the last 15 years, significant strides have been made in the diagnosis, natural history, and management of MOPDII.SummaryMOPDII is the most common and well described form of MPD. The classic features o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
78
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(84 citation statements)
references
References 65 publications
2
78
1
3
Order By: Relevance
“…MOPD II (MIM: 210720) refers to a subtype of MOPD in which patients display recognizable facial gestalt, distinct skeletal changes and sometimes cerebrovascular malformations (Hall, Flora, Scott, Pauli, & Tanaka, 2004; Willems et al, 2010). Other recognized features include rootless teeth and abnormal skin pigmentations (Kantaputra et al, 2011) while insulin resistance diabetes and abnormal hematologic indices were identified in a small number of patients (Bober & Jackson, 2017; Hall et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…MOPD II (MIM: 210720) refers to a subtype of MOPD in which patients display recognizable facial gestalt, distinct skeletal changes and sometimes cerebrovascular malformations (Hall, Flora, Scott, Pauli, & Tanaka, 2004; Willems et al, 2010). Other recognized features include rootless teeth and abnormal skin pigmentations (Kantaputra et al, 2011) while insulin resistance diabetes and abnormal hematologic indices were identified in a small number of patients (Bober & Jackson, 2017; Hall et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Unlike other forms of primary microcephaly. The eyes may show downward slanting and the jaw typically shows micrognathia (Bober & Jackson, 2017; Hall et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1993; Woods et al. 2005; Bober and Jackson 2017]. Reduction in cerebral cortex size and intellectual disability are two clinical characteristics shared by these patients.…”
Section: Centrosome Dysfunction In Neurodevelopmental Disordersmentioning
confidence: 99%
“…2008]; MOPDII patients exhibit a short stature and skeletal dysplasia in the absence of brain structural anomalies [Rauch et al. 2008; Bober and Jackson 2017].…”
Section: Centrosome Dysfunction In Neurodevelopmental Disordersmentioning
confidence: 99%